Silicosis with Various Clinical Courses in a Tunnel Worker: A Case Report - Jung-Il KIM (Tehran University of Medical Sciences, 2016)
Author reports a case of 67- years- old men referred to Donga University Hospital silicosis who had worked in tunnel drilling where presumably had been exposed to high concentration free silica for almost 20 yr. This report is considered the first in Korea to the best of our knowledge since no cases on silicosis could be reported in this occupation in reviewing various literature sources in Korea. The physician's first impression was lung cancer since the CT findings. However, it turned out to be pneumonia and silicosis. It was eventually diagnosed with silicosis and pneumonia, and tuberculosis. The patient is suffering from various clinical courses for long time.   Keywords: Silicosis, Pneumoconiosis, Tunnel worker